2023
DOI: 10.1161/str.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

The Neurovasculome: Key Roles in Brain Health and Cognitive Impairment: A Scientific Statement From the American Heart Association/American Stroke Association

Abstract: BACKGROUND: Preservation of brain health has emerged as a leading public health priority for the aging world population. Advances in neurovascular biology have revealed an intricate relationship among brain cells, meninges, and the hematic and lymphatic vasculature (the neurovasculome) that is highly relevant to the maintenance of cognitive function. In this scientific statement, a multidisciplinary team of experts examines these advances, assesses their relevance to brain health and disease, ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 235 publications
(333 reference statements)
0
18
0
Order By: Relevance
“…Tau pathology-induced activation of glial cells stimulates the trafficking of immune cells across the BBB (Figure 1), which overtime is detrimental (Blair et al, 2015;Chen et al, 2023;Majerova et al, 2019). Although correlative studies support an association of activated innate and adaptive immune cells with cognitive dysfunction, animal studies have suggested a clear cause-effect relationship between increased immune cell trafficking to the brain and cognitive decline (Iadecola, 2023).…”
Section: Neuroinflammation a Link Between Tau Pathology And Cerebrova...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tau pathology-induced activation of glial cells stimulates the trafficking of immune cells across the BBB (Figure 1), which overtime is detrimental (Blair et al, 2015;Chen et al, 2023;Majerova et al, 2019). Although correlative studies support an association of activated innate and adaptive immune cells with cognitive dysfunction, animal studies have suggested a clear cause-effect relationship between increased immune cell trafficking to the brain and cognitive decline (Iadecola, 2023).…”
Section: Neuroinflammation a Link Between Tau Pathology And Cerebrova...mentioning
confidence: 99%
“…Furthermore, the recent discovery that central nervous system antigens accumulate in dural sinuses and are presented to circulating lymphocytes, a process disrupted during neuroinflammatory states and ageing, supports and alteration of the cross-talk between the central nervous system and systemic immunity in the disease process (Iadecola, 2023;Rustenhoven, 2021). In addition, tau pathological species, through astrocytic end-feet and interstitial fluids, may spread to endothelial cells and pericytes, inducing BBB disruption and permeability to blood-borne components, including peripheral blood monocyte-derived macrophages, immunoglubulins (IgGs and IgMs) and α2-macroglobulin (Figure 1) (Canepa & Fossati, 2020).…”
Section: Neuroinflammation a Link Between Tau Pathology And Cerebrova...mentioning
confidence: 99%
“…Together, these cellular and acellular elements form the NVU responsible for maintaining the homeostasis and function of the brain microenvironment by synchronizing the energetic demand with vasodynamic changes. The NVU composition differs depending upon location within the cerebrovascular network [28,29].…”
Section: Origin and Maturation Of The Brain Vasculaturementioning
confidence: 99%
“…Adropin is neurotrophic when applied directly to cultured neurons 14 , while also preserving cerebrovascular function in situations of ischemia [19][20][21][22] . Adropin could thus support synaptic plasticity in the brain while also preventing neurovascular diseases thought to contribute to cognitive decline 23 . However, whether the results from mouse studies are translatable to the human condition has not been determined.…”
Section: Introductionmentioning
confidence: 99%